Comparing clotting factors attributes across different methods of preference elicitation in haemophilia patients. Issue 5 (25th August 2020) - Tegenge, Million A.; Belov, Artur; Moncur, Megan; Forshee, Richard; Irony, Telba
Abstract: Introduction: Emerging, systematic approaches for capturing patient input, such as preference elicitation, can provide valuable information for the benefit‐risk assessment of medical products for treating bleeding disorders, such as haemophilia. Aim: This study aims to identify existing and develop new methods to capture, rank and summarize preference scores for clotting factor therapies. Methods: Haemophilia patient preference data were compiled from studies identified through literature review and publicly available US FDA patient‐focused drug development meeting documents. Text mining was performed to identify major themes across studies. A standardized preference score was estimated and aggregated. Results: Ten preference studies that employed qualitative (n = 3), and quantitative methods (n = 7) met the inclusion criteria. Text mining of qualitative and quantitative studies revealed similar themes as the standardized preference attribute importance. We found that seven quantitative studies employed discrete choice experiments (DCE)/conjoint analysis (CA) and examined a range of 5‐12 attributes. For DCE/CA studies published prior to 2014 (n = 4), safety attributes (inhibitor and viral safety) were among the most important attributes, accounting for 46% of the total utility measured. DCE/CA studies published after 2014 (n = 3) focused on frequency of infusion and reduction of bleeding risk, accounting for 67% of the total utility. Interestingly, two studies that used different preference elicitation approaches (DCE and a monadic conjoint approach) both ranked infusion frequency as the most important attribute. Conclusions: Although there are few published patient preference studies for haemophilia, the results of this study can be viewed in the larger context of enhancing scientific methods of incorporating patient input in medical product development.